2003
DOI: 10.1002/macp.200390022
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Molecular Architecture, Morphology, and Deformation Behaviour of Styrene/Butadiene Block Copolymers

Abstract: The correlation between the molecular architecture, morphology, and micromechanical deformation behaviour of styrene/butadiene (SB) block copolymers with different architectures (linear and star block copolymers, total styrene content, ΦST = 0.74) was studied using dynamic mechanical analysis (DMA), uniaxial tensile testing, scanning force microscopy (SFM), and high voltage electron microscopy (HVEM). Deformation of the individual phases under uniaxial strain at the molecular level was monitored by Fourier tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…1A), the presence of matrix itself seems to be supportive of the moderate differentiation observed. However just as on planar substrates, terminal differentiation and a better mechanistic understanding of matrix-directed lineage specification is likely to require the improved mimicry of appropriately spaced adhesion sites (Adhikari et al, 2003;Maniadis et al, 2008) to produce optimal force production. Once attached in/on a matrix, the cell begins to pull and probe its environment, and thus extensive differences in the mechanical behavior of cells are likely to exist between planar and 3D materials.…”
Section: Designing Matrix For the Third Dimension: Microenvironment Imentioning
confidence: 99%
“…1A), the presence of matrix itself seems to be supportive of the moderate differentiation observed. However just as on planar substrates, terminal differentiation and a better mechanistic understanding of matrix-directed lineage specification is likely to require the improved mimicry of appropriately spaced adhesion sites (Adhikari et al, 2003;Maniadis et al, 2008) to produce optimal force production. Once attached in/on a matrix, the cell begins to pull and probe its environment, and thus extensive differences in the mechanical behavior of cells are likely to exist between planar and 3D materials.…”
Section: Designing Matrix For the Third Dimension: Microenvironment Imentioning
confidence: 99%
“…The latter is strongly affected by the molecular architecture. [14] Though small, a clear indication of higher crack toughness of lamellar block copolymers than that of a cylindrical one having PS matrix was observed. However, both lamellar and cylindrical (with PS matrix) block copolymers exhibited qualitatively similar linear-elastic behaviour and an unstable crack growth mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…The details of the morphology of the block copolymers used may be found in ref. [10,11,14] Electron Microscopy…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there are two T g s and only one for as-imidized and heat-drawn fiber at high temperature region, respectively. The phenomenon indicated that microphase separation existed in as-imidized fiber, which also appeared in many block copolymer systems [20,21] and was basically eliminated by heat-drawn process. The tanδ represents the energy consumption of the segmental movement, which is related to the structural homogeneity of the polymer.…”
Section: Fig 2 Tga Curves Of Pi Fibersmentioning
confidence: 99%